Biomonitoring of polycyclic aromatic hydrocarbons in firefighters at fire training facilities and in employees at respiratory protection and hose workshops - Koslitz, Stephan; Heinrich, Birgit; Käfferlein, Heiko U.; Koch, Holger M.; Pelzl, Tim; Pitzke, Katrin; Köster, Daniel; Weiß, Tobias; Harth, Volker; Brüning, Thomas; Behrens, Thomas; Taeger, Dirk (Frontiers in Public Health, 2023)
Introduction Polycyclic aromatic hydrocarbons (PAHs) are carcinogenic to humans and are formed by incomplete combustion. PAHs are always present during firefighting operations, and fire department members can be exposed to them in the workplace. Methods In this study, we analyzed 1-hydroxypyrene (1-OHP) in 36 urine samples from nine firefighters, collected before and after fire training sessions, and 32 urine samples from eight employees at respiratory protection and hose workshops. To assess breakthrough PAH exposure through personal protective equipment and potential dermal uptake, some of the workshop employees wore cotton garments under their regular workwear. Cotton samples were then examined for the presence of 17 semi-volatile and low-volatility PAHs. Results After firefighting exercises, we observed approximately a fivefold increase in mean 1-OHP concentrations in samples from firefighters, from 0.24 μg/L to 1.17 μg/L (maximum: 5.31 μg/L). In contrast, 1-OHP levels in workshop employees were found to be low, with the majority of urine samples yielding concentrations below the limit of quantification (LOQ: 0.05 μg/L, maximum: 0.11 μg/L). Similarly, low PAH levels were found on the workshop employees' cotton undergarments, with maximum concentrations of 250 and 205 ng/g for pyrene and benzo[a]pyrene, respectively. Discussion In conclusion, significant increases in 1-OHP in urine were observed in firefighters after training sessions, whereas work-related exposure remained low among workshop employees.